1962
DOI: 10.1152/jappl.1962.17.3.547
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of single elastic fibers

Abstract: The elastic properties of elastic tissue were studied in a situation which minimized the effects of extraneous connective tissue and of the position of fibers in the elastic network. Single elastic fibers were dissected free from the ligamentum nuchae of the ox and were stretched under conditions of constant temperature and salinity. The strain was an exponential function of the applied tension. Single fibers were found somewhat less stretchable than the ligaments from which they were taken. The data given can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
5

Year Published

1971
1971
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 0 publications
1
39
0
5
Order By: Relevance
“…Interestingly, however, the exponential stressstrain relationship appears not only for composite connective tissues, where architectural rearrangements contribute to it, but also for the single fibrils. Tests run on single elastic fibrils (14) show that a single fibril, teased out of the bundle which contains it, still shows increasing stiffness with increasing load.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, however, the exponential stressstrain relationship appears not only for composite connective tissues, where architectural rearrangements contribute to it, but also for the single fibrils. Tests run on single elastic fibrils (14) show that a single fibril, teased out of the bundle which contains it, still shows increasing stiffness with increasing load.…”
Section: Resultsmentioning
confidence: 99%
“…Another nuclear bag fibre is obscured by the chain fibres except at the right end of (c), where the chain fibres are Elastic fibres and reticulin of mammalian muscle spindles Two properties of elastic fibres may be important in muscle spindles. They recoil immediately after stretching [Carton, Dainauskas and Clark, 1962] and it is apparently principally because of this property that they are present in lung [Mead, 1961], artery walls [Burton, 1954;Hoffman, Grande, Gibson, Park, Daly, Bornstein and Ross, 1973], skin [Daly, 1969] and ligament [Wood, 1954]. Cooper and Daniel [1967] suggested that it is because of this ability to recoil that they are present in muscle spindles.…”
Section: Jeticulinmentioning
confidence: 99%
“…These hypotheses postulate that the PV relationship measured in the normal lung can be partitioned according to the elastic qualities of the two main connective tissue elements of the lung, elastin and collagen. Elastin, which is a highly extensible fiber and can be stretched to 130% of its resting length (47), is believed to be responsible for the shape ofthe PV curve at low and mid-lung volumes. Collagen, with a high elastic modulus allowing for fiber lengthening of only 2% (48), is believed to be responsible for the shape of PV curve at high-lung volumes.…”
Section: Discussionmentioning
confidence: 99%